FACTS OF THE CUSTOMARY LAW. INAUGURAL RECTOR'S SPEECH, DELIVERED ON THE DECEMBER 2 OF 1906; REPORT ON THE 1906/1907 ACADEMIC YEAR, ACCOMPLISHED ON THE DECEMBER 9, 1907 BY THE RECTOR, WHO PASSES HIS POST, PROF. DR. EUGEN EHRLICH - Ehrlich, Eugen; Yatsiuk, І. Ya.; Popova, T. D.; Nykyforak, M. V.; Savchuk, S. V. (Ehrlich's Journal, 2023)
The paper, published in Leipzig and Vienna in 1907, refers to the historical and comparative legal dilemma, that involves two interrelated questions: "What is the thing, that transforms life relations into legal relations, or vice versa, does not give them such status?" and "How do the factual relations transfigure to the rights and legal relations?". Its main part is divided into two blocks: positive and critical. The first one is comprised of the classification of the legal facts, and the second contains a constructive criticism of the traditional theory of customary law. In fact, this work became the basis for the 5th Section of the Grundlegung der Soziologie des Rechts [Foundation of the Sociology of Law] (1913), where the above-mentioned dilemma was formulated as follows: "What factual institutions ascend in the process of historical development of legal relations, and due to which social processes factual institutions become the legal relations?". In the positive block Eugen Ehrlich diligently, originally and thoroughly analyses the same facts as 7 years later, namely: usus, domination, possession, expression of will, and especially the question of inheritance law. Particularly interesting it is expounded the question of "actions that people commit to achieve legal results", such as the notion of the "silent trade", etc. In the critical block Eugen Ehrlich not only criticizes the traditional theory of customary law, but also advances his own. Thus, for example, he distinguishes the notion of the custom that emerged in the so-called common law in the 17th and 18th centuries, on the one hand, and his own sociological understanding of the custom. The criticism of the traditional notion is focused on the confusion of different things: social institutions and norms for the solution, derived from them. The author suggests an original theory of norms for the solution, as well as the custom. The latter case refers to the question about the element of the actual social customary law. The inaugural speech of the rector is supplemented by an Eugen Ehrlich`s report about the 1906/1907 academic year at the Chernivtsi University, which contains, among other things, interesting statistic data (e.g. about the national or confessional composition of students, etc.).